EXPERIENCE OF MANAGEMENT OF THE PATIENT WITH THE RESYNCHRONIZATION BIVENTRICULAR PACING WITHOUT DESTRUCTION OF ATRIO-VENTRICULAR NODE SUFFERING FROM CHRONIC HEART FAILURE AND PERMANENT ATRIAL FIBRILLATION - Shanina, I. V.; Volkov, D. E.; Lopin, D. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The case of cardiac biventricular resynchronization without destruction of the atrio-ventricular node in patients with chronic heart failure (CHF) and permanent atrial fibrillation (AF) is described. The observation period was 14 months. The case demonstrates that biventricular resynchronization for severe heart failure with atrial fibrillation and significant atria size with theoretical and practical impossibility of its’ transforming into the long-term persistent atrial fibrillation is a reasonable alternative of atrio-ventricular pacing. Though the destruction of the atrio-ventricular node can be delayed for a significant period of time, it should be done at the earliest opportunity. Pacemaker implantation does not cancel medical therapy, with the necessity for the latter to be according to the conducted biventricular pacing.